Water pollution observer with IOT technology / Fawwaz Najmi Nadimin - Nadimin, Fawwaz Najmi (2024)
The Water pollution Observer is a system designed to solve the growing issue of water pollution. With an ESP32 microprocessor, temperature, light, and pH sensors, the Observer's real-time monitoring system provides an in-depth depiction of the water's quality. The incorporation of the Blynk App enhances its capabilities. During its development, issues were faced and passed, demonstrating the importance of careful calibration and continuous progress. The challenges associated with creating effective environmental monitoring tools are shown by the failures and successful objectives. It is encouraging to see how the Observer may develop in the future, as more community involvement in environmental preservation and advances in technology are sure to bring big changes on how to better protect our environment. In addition to serving as a working prototype, the Water Pollution Observer provides more groundwork for upcoming developments aimed at protecting our essential water resources.